Por uma perspectiva pedagógica para intervenção da educação física com a educação infantil - Assis, Livia Carvalho de (2015)
This dissertation takes the integrative synthesis of research as an object of study that use the Sociology of the Childhood and/or the Studies with the Daily Life as an epistemological and theoretical-methodological reference for the intervention of the Physical Education with Early Childhood Education. These referential systems, in the analyzed inquiries, seek to understand the children as “subject of law”, followers of the daily life, producers of culture and protagonists in the processes of teachinglearning undertaken by the school. The main objective is to analyze these inquiries in a broader interpretative framework, formulating integrative synthesis that enable building a pedagogic perspective for intervention of the Physical Education with the Early Childhood Education. For this, it adopts the Metasynthesis Qualitative (MQ) as methodological assumption.